The role of entrepreneurship education and training programmes in advancing entrepreneurial skills and new ventures. Issue 6 (13th June 2020) - Galvão, Anderson; Marques, Carla; Ferreira, João J.
Abstract : Purpose: This study aims to understand how entrepreneurship education and training programmes (EETPs) influence the development of entrepreneurial competencies and creation of business ventures. Design/methodology/approach: The study included a questionnaire distributed to 103 EETP participants. The data were processed using SmartPLS software to construct a structural equation model. Findings: The results show, first, that the respondents' motivations have a positive impact on participation in entrepreneurship education programmes and company creation. Second, participation in these programmes positively influences individual entrepreneurial orientation and entrepreneurial skills. The findings also include that the entrepreneurship education programme under study has strengthened its participants' capacities and competencies, making these people more autonomous and facilitating their creation of new businesses. Originality/value: This study sought to contribute to a fuller empirical understanding of how EETPs affect their participants' individual entrepreneurship orientation and capacities (human resource development), thereby fostering company formation and regional development. Theoretical and practical implications are presented, with an emphasis on what needs to be done to improve EETPs.